Feto-maternal Outcome of Reverse Breech Extraction versus Dis-impaction of Fetal Head in Caesarean Section for Obstructed Labour - Safdar, Faiza; Majeed, Noreen; Nisa, Khairun; Nasir, Humaira; Mushtaq, Irum; Tariq, Shamsa (Journal of Rawalpindi Medical College, 2022)
Objectives: Obstructed labour is an obstetrical emergency with adverse feto-maternal consequences and caesarean delivery in such cases requires skillful handling of impacted fetal head. Objective of our study was to guide clinician about caesarean technique that facilitates the delivery with least complications for mother and baby. Methods: It was a randomized clinical trial with non-probability consecutive sampling conducted at –removed for blind review—from 1st july 2018 – 30th june 2020. Patients who underwent emergency cesarean section were randomized to undergo either push technique for delivery of impacted fetal head (Group A) or reverse breech extraction method (Group B) via lottery method. The data of 60 patients who fulfilled the inclusion criteria was analyzed using SPSS version 19. Maternal outcome measured were extension of uterine incision, blood transfusion, postpartum pyrexia, wound infection, postpartum hemorrhage and length of hospital stay. Fetal outcome measured were 5 minutes Apgar score, birth weight and NICU admission. Results: The results of our study showed statistically significant difference between extension of uterine incision(p-value=0.015), blood transfusion during surgery (p-value=0.021) and postpartum hemorrhage (p-value=0.020) in two groups with pull technique associated with less traumatic extension of uterine incision, less intraoperative transfusion and less PPH than push technique of fetal delivery. Length of hospital stay was also significantly less in reverse breech extraction group(p-value=0.001).More patients had postpartum pyrexia, wound infection, low 5-min Apgar score and NICU admissions in cephalic delivery group but results were not statistically significant. Conclusion: The results of our study recommend reverse breech extraction technique to be a safe alternative to conventional vaginal pushing of fetal head especially regarding maternal outcomes during caesarean section of patients with obstructed labour for fetal delivery. Key words: Obstructed labour, impacted fetal head, reverse breech extraction, caesarean section